Pengaruh Problem Based Learning (PBL) Terintegrasi Socio-Scientific Issues (SSI) terhadap Literasi Lingkungan Siswa SMA Kelas X - Dwie Jihan Fadilla; Syarifah Widya Ulfa (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aims to determine the impact of problem-based learning (PBL) on high school students' environmental literacy by considering socio-scientific factors. The main focus of this research is the environmental literacy of students at SMA Plus Sedayu Nusantara in Medan Marelan District. The method used is a quasi-experimental design with a non-equivalent control group and a quantitative approach. The study population consisted of 62 tenth-grade students at SMA Plus Sedayu Nusantara, divided into two groups: the experimental class (X MIA1, 31 students) and the control class (X MIA2, 31 students). Research instruments included multiple-choice tests, essays, and attitude questionnaires. Data analysis was performed using an independent t-test with the SPSS v24 software. The results showed that the average learning outcome of the experimental class increased from 55 to 78 after treatment, while the control group increased from 47 to 57. Descriptive statistical analysis indicated a difference in the average environmental literacy levels between the experimental and control groups. The t-test results confirmed that the average score of the experimental class was significantly higher than that of the control class. In conclusion, problem-based learning (PBL) is effective in improving high school students' environmental literacy by considering socio-scientific factors. Keywords: Environmental Literacy, Problem-Based Learning, Socio-Scientific Issues